MANAJEMEN PENGELOLAAN KINERJA KEUANGAN KOPERASI SEKOLAH SMK SWAKARYA PALEMBANG - Diana Widhi Rachmawati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
School cooperatives are an economic forum with two or more members and work together to achieve common interests, an formed also established in a school environment whose members consist of school students covering various levels of education in accordance with the current level of education, for example primary school cooperatives, junior high school cooperativas, high school or vocational schools and so on. Financial statement analysis is a tool and technique used in analyzing financial statements that have general objectives relating to data and are closely related to producing estimates as well as conclusions as well as benefits in business analysis. Financial report analysis which in fact is also used in this study includes ratio analysis methods namely ratio of liquidity, solvency, activity and profitability. Researchers in this case use quantitative research methods, namely a research method basedon the philosophy of positivism as well as used for research that focuses on a particular population or sample, the sampling technique is done randomly, in addition, the use of research instruments as a data collection tool, while data analysis is quantitative statitics withthe aim to test the hypothesis that has been set. Research sample is SMK Swakarya Palembang cooperative. The achiement of the final results obtained from this study is SMK Swakarya Palembang cooperative is likuid, because there is no looan to other parties from outside and there is no establishment of a business unit of buying and selling school supplies but not only moves in the savings and loan business unit, is still quite solvable because it is only moving in one area of the work unit that is savings and loans, not profit because there are still many funds that are still in the hands of its members and good enough activity because the funds continue to spin from members lairn to other members. The hope for school cooperatives can develop works units again so as to realize the prosperity of its members.